2021
DOI: 10.3390/molecules26113439
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazoles and Pyrazolines as Anti-Inflammatory Agents

Abstract: The five-membered heterocyclic group of pyrazoles/pyrazolines plays important role in drug discovery. Pyrazoles and pyrazolines present a wide range of biological activities. The synthesis of the pyrazolines and pyrazole derivatives was accomplished via the condensation of the appropriate substituted aldehydes and acetophenones, suitable chalcones and hydrazine hydrate in absolute ethanol in the presence of drops of glacial acetic acid. The compounds are obtained in good yields 68–99% and their structure was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…[151] Pyrazolines bearing phenyl and benxyloxy substitutions at C3 and C5 exerts greater anti-inflammatory effect than the standard indomethacin, and this can be considered for developing newer leads. [152] From the above findings it is concluded that the phenyl ring with electron donating group substitution attached to the pyrazole moiety is essential for excellent COX-2 inhibitory activity.…”
Section: Miscellaneousmentioning
confidence: 96%
See 1 more Smart Citation
“…[151] Pyrazolines bearing phenyl and benxyloxy substitutions at C3 and C5 exerts greater anti-inflammatory effect than the standard indomethacin, and this can be considered for developing newer leads. [152] From the above findings it is concluded that the phenyl ring with electron donating group substitution attached to the pyrazole moiety is essential for excellent COX-2 inhibitory activity.…”
Section: Miscellaneousmentioning
confidence: 96%
“…Compound bearing 3‐phenoxy and 3,5‐dimethyl benzyloxy benzaldehyde at acetohydrazide on pyrazole nucleus was found to exhibit excellent anti‐inflammatory activity with IC50<0.78 μM each compared to 5.6 μM of diclofenac indicating that the electron withdrawing groups on the phenyl ring of pyrazole possess excellent anti‐inflammatory activity [151] . Pyrazolines bearing phenyl and benxyloxy substitutions at C3 and C5 exerts greater anti‐ inflammatory effect than the standard indomethacin, and this can be considered for developing newer leads [152] …”
Section: Miscellaneousmentioning
confidence: 99%
“…Simultaneously, circulation of leukocytes and endothelial cells are provided to the injured/infected tissue. Nonsteroidal antiinflammatory drugs target the phase of the inflammation by inhibiting cyclooxygenase (COX) enzymes [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs display their activities on both of the COX isozymes. Since the inhibition of the COX-1 enzyme is responsible for the gastrointestinal and renal adverse effects of NSAIDs, it was thought that these side effects could be eliminated only by inhibiting the COX-2 enzyme [2]. When selective inhibition of the COX-2 enzyme appeared to cause serious cardiovascular problems, a balanced inhibition of both isozymes became important [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation